ANATOMY OF ORAL ACADEMIC PRESENTATION SKILLS: A COURSE DESIGN FOR COLLEGE STUDENTS OF ENGLISH DEPARTMENT - Akbar Akbar (Institut Agama Islam Negeri Palopo, 2017)
The core concern of teaching in tertiary education is to enable college students to experience higher order of thinking in knowledge exploration that shape the students academic identity. The focus of language proficiency in this context is not for communicative use in general but more specific to academic purposes such as research dissemination. This article explores essential components of a course design of Academic presentation Skills to facilitate research based learning. This article first discusses the inclusion of research based learning and teaching framework into Oral Academic Presentation Skills (OAPS) course. Before it portrays the course design of Research Based-Academic Presentation Skills, this Article identifies the drawbacks and the benefits of the course design. Furthermore, essential components of the OAPS such as learning objectives and, technology and online materials are discussed in order to provide a clear portrait of OAPS. Implication and suggestions for future researchers and course designers are also discussed.